Dietary supplements, harm associated with synthetic adulterants and potential governance solutions - Manning, Louise (Crime, law and social change, 2022)
Intentional adulteration of dietary supplements with undeclared synthetic drugs illegally enhances the supplement’s purported efficacy and is a growing global crime issue that can cause actual harm to unsuspecting victims. The aim of this research is to identify the potential adulterants of interest in dietary supplement adulteration and then to consider what governance systems can be implemented to reduce the likelihood of such practices occurring. Firstly, existing academic and grey literature is iteratively reviewed to define and outline the challenge of dietary supplement adulteration. Three types of supplement are considered in particular, namely those supplements promoted for weight loss, sexual enhancement, and muscle building. Two regulatory databases (the European Union Rapid Alert System for Food and Feed database and the United States Food and Drink Administration database of Recalls, Market Withdrawals, & Safety Alerts databases) are used to determine the incidence of adulteration by product type and the nature of the adulterants being used. The role of pharmacovigilance governance systems that focus on dietary supplements is considered.